Reseña de Pedro Calderón de la Barca, «La exaltación de la cruz», ed. Ignacio Arellano, Madrid / Frankfurt am Main, Iberoamericana / Vervuert, 2022, 216 pp. ISBN: 978- 84-9192-260-5 (Iberoamericana) ISBN: 978-3-96869-255-5 (Vervuert) - Jorge Ferreira Barrocal (Hipogrifo: Revista de Literatura y Cultura del Siglo de Oro, 2022)
Reseña de Pedro Calderón de la Barca, La exaltación de la cruz, ed. Ignacio Arellano, Madrid / Frankfurt am Main, Iberoamericana / Vervuert, 2022, 216 pp. ISBN: 978- 84-9192-260-5 (Iberoamericana) ISBN: 978-3-96869-255-5 (Vervuert)